THE CONTENT OF THE IMPROVEMENT OF OUTSIDE THE CLASSROOM WORK IN PRIMARY GRADES (World Bulletin of Social Sciences, 2023)
The fundamental reforms implemented in the field of education in our country are aimed at forming a well-rounded human personality and fully correspond to the national interests and noble goals of our people. The requirements of the national curriculum are mainly aimed at giving new meaning and content in the minds of young people, forming a vital position in it. Because young people see the national idea as an important means of ensuring the country's development, peace and well-being of the people. Young people are naturally curious about ideas and are quick to give in to them. Highly spiritual people also know the ways of cultural marriage. As a product of high cultured taste, any spiritual creation is distinguished by its nobility. That is why high human taste and high culture lie in the essence of spiritual beauty